Hyperuniform disordered metal-insulator-metal gap plasmon metasurface near perfect light absorber - Kim, Wonkyu; Simpkins, Blake S.; Guo, Hong; Hendrickson, Joshua R.; Guo, Junpeng (Optical materials express, 2021)
In this work, we first introduce hyperuniform disordered patterns to a metal-insulator-metal gap plasmon metasurface and demonstrate enhanced wideband light absorption in the visible and near-infrared spectral region. Measurement of optical reflectance from fabricated periodic, hyperuniform disordered, and random pattern gap plasmon metasurface devices has revealed the origins of the two resonance modes of the gap plasmon metasurface structure: a localized gap plasmon resonance mode and a non-local guided optical resonance mode. The technique of using hyperuniform disordered patterns for investigating complex resonance modes of structured materials can be used for design of a variety of new metamaterials.